Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1111/j.1467-8276.2008.01144.x
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Payments and Land Concentration: A Semiparametric Spatial Regression Analysis

Abstract: Over the last twenty years, both crop production and agricultural payments have shifted toward larger operations. This study examines whether payments from federal farm programs contributed to increased concentration of cropland and farmland. Using zip code—level data constructed from the microfiles of the 1987–2002 agriculture censuses we examine the association between government payments per acre and subsequent growth in land concentration. A semiparametric generalized additive model (GAM) controls for loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…At the same time, yield losses might induce farmers to purchase less outside goods and result in fewer investments. Roberts & Key (2008) have also shown that larger government payments result in consolidation in the farm sector, thereby increasing average farm size. An increase in farm size might lead to efficiency gains and hence reduce the demand for services and goods outside the agricultural sector.…”
Section: Further Resultsmentioning
confidence: 99%
“…At the same time, yield losses might induce farmers to purchase less outside goods and result in fewer investments. Roberts & Key (2008) have also shown that larger government payments result in consolidation in the farm sector, thereby increasing average farm size. An increase in farm size might lead to efficiency gains and hence reduce the demand for services and goods outside the agricultural sector.…”
Section: Further Resultsmentioning
confidence: 99%
“…Zepeda, 1995;Pietola et al, 2003;Yee and Ahearn, 2005;Breustedt and Glauben, 2007;Key and Roberts, 2007;Möllers and Fritzsch, 2010) and were the focus of other studies (e.g. Ahearn et al, 2005;Roberts and Key, 2008;Piet et al, 2012). Zepeda (1995), Pietola et al (2003) and Glauben et al (2006) found no significant impact of agricultural programmes on farm exits.…”
Section: Agricultural Public Policiesmentioning
confidence: 89%
“…Similarly, the average area per farm has increased from 9.2 ha in 2003 to 13.7 ha in 2010, which indicates that land consolidation in taking place. It follows global agribusiness structural change, of crop production shifting to larger operations, due to changes in technology and factor prices (Roberts and Key, 2008). According to 2010 data for Lithuania, majority of the land was owned by farmers who actually worked on the land: 1,406,610 ha (51.3%), while 1,273,390 (46.4%), was cultivated by tenants.…”
Section: General Overview Of Agricultural Sectormentioning
confidence: 99%